Troop Takeover and Reproductive Success of Wild Male Japanese Macaques on Yakushima Island (Macaca fuscata yakui) - Hayakawa, Sachiko; Soltis, Joseph (International Journal of Zoology, 2011)
Troop takeover is common in one-male primate groups, but there are few reports in multimale groups. Japanese macaques (Macaca fuscata) form multimale groups and males commonly join troops at the bottom rank. On Yakushima island, however, where group size is relatively small, entrance into groups at the alpha position is also observed. This paper reports on the general features of troop takeover, on the predictors of takeover events, and on the reproductive success of takeover males. Troop takeovers occurred only in the mating season; nontroop males (NTMs) did not cooperate with each other; former alpha males were rarely expelled from the troop; new alpha males did not commit infanticide; new alpha male tenure in the group was usually less than two years. Logistic regression analysis showed that the number of NTMs associating with a troop predicted the occurrence of troop takeover. Paternity discrimination revealed that 33.3% (3/9) of takeover males succeeded in siring offspring. Contrary to this low success rate, binary logistic regression analysis revealed that the takeover males can expect higher reproductive success compared to troop males. Entering a troop and out-competing the alpha male is one of many available strategies to attain reproductive success in male Japanese macaques.